MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN TEKS NARRATIVE DENGAN MODEL PEMBELAJARAN THINK PAIR AND SHARE PADA SISWA KELAS X DKV-2 SMK NEGERI 1 JUWIRING - ABDUL AZIS (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2023)
The purpose of this study is to improve the ability to read and understand narrative texts in English lessons using the think pair and share learning model for Class X DKV-2 students of Juwiring 1 State Vocational School in the even semester of the 2022/2023 Academic Year. In this study, the research subjects were students of class X DKV-2 with a total of 35 students. This research is a classroom action research (CAR) and the data is presented through qualitative and quantitative descriptive data. This research was conducted in two cycles. Each cycle consists of 4 stages, namely: planning, implementation, action and reflection stages. Learning process data, each cycle was analyzed descriptively qualitatively. While the learning outcomes data were analyzed in a quantitative descriptive manner. This Classroom Action Research was conducted using the think pair and share learning model. Before carrying out the action, the researcher begins by conducting a reading comprehension test of narrative text as an initial reflection followed by action in cycle 1 and cycle 2. Some of the results or conclusions from the results of this study are (1) The score of the ability to read comprehension test of narrative text in classical completeness is 31, 43% in cycle 1 increased to 89.67% in cycle 2, (2) The think pair and share learning model can be used as a reference as a learning model in improving students' reading comprehension comprehension of narrative texts. ABSTRAKTujuan dari penelitian ini adalah meningkatkan kemampuan membaca pemahaman teks narrative pada pelajaran Bahasa Inggris dengan model pembelajaran think pair and share bagi siswa Kelas X DKV-2 SMK Negeri 1 Juwiring pada semester genap Tahun Pelajaran 2022/2023. Dalam penelitian ini yang menjadi subyek penelitian adalah siswa kelas X DKV-2 dengan jumlah 35 siswa. Penelitian ini merupakan penelitian tindakan kelas (PTK) dan datanya dipaparkan melalui data deskriptif kualitatif dan kuantitatif. Penelitian ini dilaksanakan dalam dua siklus. Setiap siklus terdiri dari 4 tahap yaitu: tahap perencanaan, pelaksanaan, tindakan dan refleksi. Data proses pembelajaran, setiap siklus dianalisis secara deskriptif kualitatif. Sedangkan data hasil pembelajaran dianalisis secara deskriptif kuantitatif. Penelitian Tindakan Kelas ini dilakukan dengan menggunakan model pembelajaran think pair and share. Sebelum melakukan tindakan, peneliti awali dengan mengadakan tes kemampuan membaca pemahaman teks narrative sebagai refleksi awal yang dilanjutkan tindakan pada siklus 1 dan siklus 2. Beberapa hasil atau kesimpulan dari hasil penelitian ini adalah (1) Skor tes kemampuan membaca pemahaman teks narrative ketuntasan klasikal 31,43% pada siklus 1 meningkat menjadi 89,67% pada siklus 2, (2) Model Pembelajaran think pair and share dapat dijadikan acuan sebagai model pembelajaran dalam meningkatkan kemamapuan membaca pemahaman teks narrative oleh siswa.